Studies of the decays D^0 → K_S^0K^-π^+ and D^0 → K_S^0K^+π^- - Collaboration, CLEO; Insler, J; Muramatsu, H; Park, C; Pearson, L; Thorndike, E; Ricciardi, S; Thomas, C; Artuso, M; Blusk, S; Mountain, R; Skwarnicki, T; et al. (2012)
The first measurements of the coherence factor R_{K_S^0Kπ} and the average strong--phase difference δ^{K_S^0Kπ} in D^0 → K_S^0 K^\mpπ^± decays are reported. These parameters can be used to improve the determination of the unitary triangle angle γ in B^- → \widetilde{D}K^-$ decays, where $\widetilde{D}$ is either a D^0 or a D^0-bar meson decaying to the same final state, and also in studies of charm mixing. The measurements of the coherence factor and strong-phase difference are made using quantum-correlated, fully-reconstructed D^0D^0-bar pairs produced in e^+e^- collisions at the ψ(3770) resonance. The measured values are R_{K_S^0Kπ} = 0.73 ± 0.08 and δ^{K_S^0Kπ} = (8.3 ± 15.2)$^°$ for an unrestricted kinematic region and R_{K*K} = 1.00 ± 0.16 and δ^{K*K} = (26.5 ± 15.8)$^°$ for a region where the combined K_S^0 π^± invariant mass is within 100 MeV/c^2 of the K^{*}(892)^± mass. These results indicate a significant level of coherence in the decay. In addition, isobar models are presented for the two decays, which show the dominance of the K^*(892)^± resonance. The branching ratio B(D^0 → K_S^0K^+π^-)/B(D^0 → K_S^0K^-π^+) is determined to be 0.592 ± 0.044 (stat.) ± 0.018 (syst.), which is more precise than previous measurements.